PENGARUH KETERSEDIAAN BARANG DAN DISPLAY PRODUK TERHADAP STORE ATMOSPHERE SERTA IMPLIKASI PADA IMPULSE BUYING - Rahayu, Fifi; Annisa Fitri, Intan; Sarwoto, Sarwoto; Cai Cen, Cia (CV. Lafadz Jaya, 2024)
This research aims to find out whether the availability of goods and product displays have an effect on impulse buying, the availability of goods and product displays have an effect on store atmosphere, and the availability of goods and product displays have an effect on store atmosphere on impulse buying. The research method used uses quantitative methods with Smart PLS 3.0 software. The sampling technique used was non-probability sampling with accidental sampling technique. Data were collected using questionnaires and literature studies from 90 respondents who had purchased and used goods at Panglong UD Sinar Maju. The data analysis method in this research uses instrument test analysis (validity test and reliability test), goodness of fit (GoF) test, multiple linear regression analysis, determinant coefficient analysis, and hypothesis testing. The results of the research are: 1. The influence of the availability of goods is rejected on impulse buying. 2. Availability of goods is stated as acceptable to the store atmosphere. 3. Product displays are declared objectionable to the store atmosphere. 4. Product displays are declared acceptable for impulse buying. 5. Store atmosphere is stated to be resistant to impulse buying. 6. Availability of goods for impulse buying through the store atmosphere is declared rejected. 7. Product displays for impulse buying through store atmosphere are declared rejected.